Pengaruh Community Effect dan Brand Ambassador Terhadap Keputusan Pembelian Produk Susu Ultra Milk Melalui Mediasi Brand Image (Studi Pada Komunitas Midzy Iindonesia - Salsabila, Naila Nisa; Purnamasari, Devi (Peneliti.net, 2023)
The use of brand ambassadors has become an important part in the world of marketing, a brand ambassador is expected to represent the desires and needs of consumers and can have a positive influence on the brand of a product and a positive image for the company. The purpose of this study was to determine how much influence the community effect and brand ambassador have on the purchase decision of ultra milk, milk products through brand image mediation. Research using quantitative methods with descriptive research type. The population in this study was the Indonesian Midzy Community, which consisted of 120 respondents. Samples were taken using the probability sampling method and the analysis technique used SEM AMOS. Based on the results of the study, the two community effect variables and brand ambassadors only contributed 24% to brand image and 19% to purchasing decision.